Improved manufacturability and in vivo comparative pharmacokinetics of dapagliflozin cocrystals in beagle dogs and human volunteers - Cho, Sangho; Lee, Jeongwook; Yoo, Yongwon; Cho, Minyong; Sohn, Seil; Lee, Beom Jin (Pharmaceutics, 2021)
Dapagliflozin (DAP), which improves glycemic control in patients with type 2 diabetes mellitus, has poor physical properties against heat and moisture, thus hindering its manufacturing potential. The superior physicochemical properties of a recently developed cocrystal of DAP and citric acid (DAP cocrystal) in comparison with those of DAP and Forxiga®, a patented solvate form with propandiol monohydrate, were identified via structural analysis and moisture sorption isotherm. For the first time, the formulation, manufacturability, and in vivo bioavailability of DAP cocrystals were successfully investigated to develop oral dosage forms that substitute Forxiga®. The intrinsic dissolution rate of DAP cocrystal was controlled by varying particle size distribution. Unlike the direct compression (DC), roller compaction (RC) was more preferable to obtain good flowability of dry granules for a continuous manufacturing system. The cocrystal structure was maintained throughout the stability assessment period. In Vitro dissolution pattern differences of the optimized DAP cocrystal tablet with RC and the reference tablet, Forxiga® 10 mg, were pharmaceutically equivalent within 5% in four different media. Furthermore, comparative pharmacokinetic analysis confirmed that a 10 mg DAP cocrystal tablet with RC was bioequivalent to a 10 mg Forxiga® tablet, as assessed in beagle dogs and human volunteers.
Keywords: Cocrystal; Comparative pharmacokinetics; Dapagliflozin; Dissolution; Dry granulation; Manufacturability; Stability